Spatial and temporal effects of China’s digital economy on rural revitalization - Zhou, Xiangjun; Du, Meng; Dong, Hai (Frontiers in Energy Research, 2023)
The paper constructs an evaluation index system of China’s digital economy and rural revitalization development, including 46 indicators of digital economy and rural revitalization subsystem, and analyzes the impact of China’s digital economy on rural revitalization by combining spatial Markov analysis method and spatial econometric model, and finds that:① The spatial heterogeneity of rural revitalization pattern is obvious, and the difference between north and south is more prominent, and the spatial clustering characteristic of rural revitalization pattern The spatial clustering characteristics are obvious, and the degree of clustering decreases with the increase of the spatial distance threshold. ② Digital economic development can significantly promote the level of rural revitalization in the region, and this finding is found to be robust by introducing the exogenous policy shock test of the Outline of Digital Rural Development Strategy, and digital economic development has a significant spatial siphon effect and can influence the level of rural revitalization in neighboring regions. Considering spatial heterogeneity, the regression results based on the multi-distance economic circle show that the siphoning effect of digital economy on rural revitalization in other regions peaks at 700 km ③Main contribution: It reveals that implementing a differentiated digital economy development strategy and enhancing the radiation of polarized regions are important for reducing regional differences in digital economy and rural revitalization to realize the coordinated development of China’s digital countryside.